Effect of the coexistence of sodium caseinate and Tween 20 as stabilizers of food emulsions at acidic pH - Perugini, Luisa; Cinelli, Giuseppe; Cofelice, Martina; Ceglie, Andrea; Lopez, Francesco; Cuomo, Francesca (Colloids and surfaces, B, Biointerfaces, 2018)
[Display omitted] •Nanoemulsions stabilized by sodium caseinate lose their stability at acidic pH.•The stability is improved using a blend of caseinate and Tween 20 as emulsifiers.•Emulsion prepared with the blend is sterically and electrostatically stabilized. In the present investigation the properties of edible nanoemulsions were studied. Sodium caseinate represents a good candidate for food emulsion preparations thanks to its surface-active properties and because it is perceived as a natural product by consumers. Nevertheless, it is very sensitive to acidic pH close to its isoelectric point and, if used as emulsion stabilizer, this aspect can negatively affect the emulsion stability. In order to prevent this drawback, sodium caseinate was used in combination with a non-ionic surfactant (Tween 20) as emulsifier of oil/water nanoemulsions. For these reasons, nanoemulsions stabilized by Tween 20, sodium caseinate and by a blend of the two emulsifiers were studied and compared according to their response to pH variations. Nanoemulsions were characterized for size of the dispersed phase with variation of time and temperature, for their rheological properties, for surface charge as a function of pH and for protein fluorescence. Noticeably, it was ascertained that, at pH close to caseinate isoelectric point, emulsions stabilized with the blend of caseinate and Tween 20 were more stable, compared with emulsions stabilized only with sodium caseinate. Such behavior was explained according to the composition of the emulsifiers at the oil/water interface where, at acidic pH, the presence of Tween 20 ensured the steric stabilization thus improving the role of sodium caseinate as emulsion stabilizer.